2001
DOI: 10.1143/jjap.40.3614
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Spectra of ZnO-CoO Alloy Semiconductors

Abstract: Photoacoustic spectra (PA) of Zn 1−x Co x O alloy semiconductors sintered as powdered samples were measured to estimate the optical absorption. Photoacoustic spectroscopy (PAS) is insensitive to the light scattering effects on the samples. CoO molecular percentages in the alloy were changed from 0 to 20 mol%. The samples were sintered at 600 or 950 • C for 24 h in a quartz glass tube. From the PA spectra in the short wavelength region, we plotted (ρhν) 2 vs hν and estimated the band-gap energy (E g ) of the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…It could be supposed that the detected lower value of the energy -2.95 eV, could be ascribed to the gap of Zn 1-x Co x O. This value is in agreement with the observed decreases of E g with an increase of CoO in the Zn 1-x Co x O alloys [19]. Further investigation should be performed to clarify the observation.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…It could be supposed that the detected lower value of the energy -2.95 eV, could be ascribed to the gap of Zn 1-x Co x O. This value is in agreement with the observed decreases of E g with an increase of CoO in the Zn 1-x Co x O alloys [19]. Further investigation should be performed to clarify the observation.…”
supporting
confidence: 86%
“…Actually, the inverse slope of the ln α vs. energy plot in the range below the ZnO energy gap (<3.35 eV) gives a value of the band tail width of about 400 meV which seems to be a very high value for the Urbach tail. We can not pinpoint the true nature of the defects that control the absorption in this wavelength range, although it likely to be associated with Zn vacancies and/or interstitial Co 3+ , as supposed in [18,19]. Another hypothesis could also be advanced.…”
mentioning
confidence: 84%
“…The PA signal intensity between 370 and 410 nm of all the samples steeply decreases; this decrease is caused by the fundamental absorption of ZnO. 8,9) The ZnO sample shows an almost flat PA spectrum between 410 and 650 nm, indicating that there is no occurrence of nonradiative transition in the visible range. The other samples doped with Pr, Nd, and Ho show peaks in each PA spectrum, which are represented by…”
mentioning
confidence: 95%
“…Such a theoretical approach is important in elucidating the green luminescence mechanism for intrinsic ZnO, 6,7) although many possible mechanisms have been proposed. By photoacoustic (PA) spectroscopy, 8,9) we have studied the nonradiative transition originating in Pr 3þ in ZnO powders, 10) which were prepared by a dry reaction within an evacuated sealed silica glass tube. 11) We found that the inner state of Pr 3þ in the ZnO matrix depends on Pr content and sintering temperature.…”
mentioning
confidence: 99%
“…15,16) PAS is a very useful technique for studying the nonradiative transition in semiconductors, because it enables the direct detection of the transition. Thus, it is widely applied to detecting a nonradiative process in inorganic semiconductors, such as, porous Si, 17) Co-doped ZnO powders, [18][19][20] and oxide thin films. 21,22) We thought that PAS was also appropriate for evaluating organic semiconductors and studying the organic material, PTCDA films; the difference in the nonradiative recombination of PTCDA films deposited on different substrates was observed.…”
Section: Introductionmentioning
confidence: 99%